Detection of enteric bacteria in two groundwater sources and associated microbial health risks - Adewale O. Olalemi (IWA Publishing, 2021)
The microbial quality of two groundwater sources (well and borehole) and associated risks were quantitatively assessed. Water samples from the selected borehole and well were collected over a period of 12 weeks (n = 48). The concentrations of Escherichia coli, faecal coliforms, Salmonella, Shigella, Clostridium, Bifidobacterium and Campylobacter were determined using standard microbiological methods, which involve the use of a membrane filter technique. The water samples were filtered through a 0.45 μm membrane filter using vacuum pump pressure and plated on selective agar for the bacteria under test. The number of colonies of the bacterial growth observed after the incubation period was counted and recorded. The physicochemical properties of the water were determined using standard methods. The risk of Salmonella, Shigella, Clostridium and Campylobacter infections resulting from the ingestion of water from the borehole and well was estimated. The results showed that the levels of enteric bacteria in the borehole were higher than those in the well. The mean levels of E. coli in water from the borehole and well were 3.3 and 1.7 log10 cfu/100 ml, respectively, and exhibited a negative relationship with salinity (r = −0.53). The estimated risks of infection associated with the pathogens in water from the borehole and well were greater than the acceptable risk limit of 10−4 and followed this order Clostridium < Salmonella < Campylobacter < Shigella. The findings of this study suggest recent and continuous faecal contamination of the two groundwater sources, thus exposing the residents relying on the water for drinking to potential risks of gastrointestinal infections. HIGHLIGHTS Levels of E. coli, faecal coliforms, Salmonella, Shigella, Clostridium, Bifidobacterium and Campylobacter in the borehole and well water exceeded 1.5 log.; Temperature and Salmonella had direct relationship while electrical conductivity and Clostridium had inverse relationship in borehole and well water.; The risks of gastrointestinal illness from consumption of water from the borehole were greater than the well.; Estimated risks of infection associated with Salmonella, Shigella, Clostridium and Campylobacter in water samples were greater than acceptable risk limit of 10−4.; The risks of infection for Shigella and Campylobacter were more than 10 times greater than for Salmonella.;